Saúde ambiental e promoção da saúde no bairro Chamanculo "C", Maputo - Moçambique - Ramos, Joaquim Dalques (2017)
The present study consists of a diagnosis of health and quality of life conditions of the population of Chamanculo C neighborhood, in the city of Maputo, capital of Mozambique. The research originated from a project of scientific academic cooperation between the Federal University of Uberlândia - UFU in Brazil and the Pedagogical University - UP, in Mozambique. The objective of this study was to understand how people live and get sick and die, to know the problems and health needs, with information about population and place, evidenced by cultural, social, economic, epidemiological and environmental characteristics, social aggregation and style Life, public policies, among other factors that interfere directly or indirectly in health and well-being, for the elaboration of intersectoral public policies aimed at disease prevention and health promotion. The diagnosis was made through a population survey of 350 families, focusing on the family group, considering the dwelling and the surroundings of the neighborhood. Sampling was randomized and stratified. Initially the neighborhood was divided into quadrants (strata) and then a simple random sampling was performed on each of them. The data were processed by the EPI INFO (Version 3.5.2) computer system for the elaboration of graphs and statistical analyzes. The conclusion of the paper is the precarious conditions of health and social vulnerability in Chamanculo C can only be mitigated by strengthening social capital resources and local public policies to improve the quality of life of the population. This diagnosis of health situation and quality of life can constitute a basic platform for the elaboration of intersectoral policies aimed at the prevention of diseases and health promotion in the territory.